HAK IMUNITAS ADVOKAT INDONESIA DALAM PERSPEKTIF PENEGAKKAN HUKUM DAN KEADILAN DI ERA REVOLUSI INDUSTRI 4.0â€ - Jiwantara, Firzhal Arzhi (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2019)
ince the birth of Law Number 18 Year 2003 Regarding Advocates on December 21, 2004, it is a form of appreciation for Advocates who are not only working but struggling to find noble justice and until finally being recognized as a Profession. Then from Law Number 18 Concerning Advocates contained the